2020
DOI: 10.1002/hed.26381
|View full text |Cite
|
Sign up to set email alerts
|

Core needle biopsy for diagnosing lymphoma in cervical lymphadenopathy: Meta‐analysis

Abstract: Background The diagnostic yield of core needle biopsies (CNB) in cervical lymphadenopathy for lymphoma diagnosis is controversial. The aim of this study was to calculate the accuracy of cervical CNB in diagnosing lymphoma. Methods We conducted a meta‐analysis of all studies on patients presenting with cervical lymphadenopathy and referred to CNB. Patients with a diagnosis other than lymphoma were excluded. All cases diagnosed with lymphoma sufficient to guide treatment based on CNB outcome were considered accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
0
15
0
3
Order By: Relevance
“…Some studies have confirmed that lymphoma rarely occurs necrosis, usually caused by trophoblast artery embolization resulting in coagulative necrosis. CEUS can intuitively show the necrotic area in lymphoma [ 10 , 14 17 ], coagulative necrosis was described in the pathologic findings of lymphoma cases with intermittent specimens in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies have confirmed that lymphoma rarely occurs necrosis, usually caused by trophoblast artery embolization resulting in coagulative necrosis. CEUS can intuitively show the necrotic area in lymphoma [ 10 , 14 17 ], coagulative necrosis was described in the pathologic findings of lymphoma cases with intermittent specimens in this study.…”
Section: Discussionmentioning
confidence: 64%
“…81 However, other studies have shown far lower diagnostic yield. A recent metanalysis of CNB for diagnosis of lymphoma in cervical lymphadenopathy found a rate of actionable lymphoma diagnoses as low as 30% (range 30%-96.3%) 87 and a recent study of 457 biopsies (339 excisional and 118 CNB) found that only 56.8% of CNB samples contained adequate tissue compared to 96.8% of excisional biopsy samples. 88 In this rapidly evolving field, the American Society for Clinical…”
Section: Gold Standard Sampling Technique Most Invasive and Least Ava...mentioning
confidence: 99%
“…Numerous complications including bleeding, bruising, discomfort, and infection are associated with core biopsy. In spite of this, the non-availability of a surplus amount of tissue is another problem associated with this diagnosis [ 46 ].…”
Section: Reviewmentioning
confidence: 99%